Kelayakan Media Peraga untuk Pembelajaran Analisis Kerusakan Sistem Wiper dan Washer - Heri Setiawan; Febrian Arif Budiman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to: 1) evaluate the feasibility of the teaching media developed to support learning on the topic of wiper and washer systems; and 2) examine the extent to which the media can improve student learning outcomes. This research uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model which includes five stages, namely analysis, design, development, implementation, and evaluation. The research design used was One Group Pretest-Posttest. The research participants were students of class XI of Automotive Light Vehicle Engineering (TKRO) at SMK Dr. Sutomo Temanggung. The research subjects consisted of 29 students in grade XI TKRO 3 who acted as a control group and 28 students in grade XI TKRO 2 as an experimental group. Based on the results of validation by material experts and media experts, the wiper and washer system teaching media developed was declared to meet the eligibility criteria to be applied in the learning process. The measurement of learning outcome improvement is carried out through pre-test and post-test, then analyzed using the N-Gain formula. The results of the analysis showed that both the experimental group and the control group experienced an increase in learning outcomes at almost the same rate. The N-Gain value in the experimental class reached 0.679 or equivalent to 67% which was included in the category of "moderate" improvement. Meanwhile, the control class obtained an N-Gain value of 0.678 or 67% which is also included in the "moderate" improvement category. These findings indicate that the props of the wiper and washer systems are feasible and quite effective to be used in learning automotive engineering.